Comparison of post-discharge mortality and medical expenditures in COVID-19 patients according to mechanical ventilation and extracorporeal membrane oxygenation use: The LIFE study - Jun Kawabata; Kenichi Goto; Megumi Maeda; Haruhisa Fukuda (PLoS ONE, 2026)
Outcomes related to health status and economic burden among patients who experienced critical COVID-19 remain insufficiently studied. We examined 180-day post-discharge mortality and total medical expenditures in COVID-19 patients according to their use of mechanical ventilation (MV) or extracorporeal membrane oxygenation (ECMO) during hospitalization. Using medical claims data from a Japanese municipality, this retrospective cohort study analyzed hospitalized COVID-19 patients who were discharged between April 1, 2020 and September 30, 2021. Patients were categorized into an MV/ECMO group (indicating severe disease) or a non-MV/ECMO group. Their differences in mortality and expenditures were compared using the χ 2 test and Mann–Whitney U test, respectively. A Cox regression analysis was performed to calculate the hazard ratios of MV/ECMO use for mortality, and a generalized linear model with gamma distribution was constructed to examine the association between MV/ECMO use and expenditures. The covariates included age, sex, comorbidities, and length of stay. The MV/ECMO group had significantly higher mortality (16.0% vs. 11.1%, p = 0.002) and expenditures ($8,732 vs. $3,460, p < 0.001) than the non-MV/ECMO group. MV/ECMO use was significantly associated with higher mortality (hazard ratio: 1.66, 95% confidence interval: 1.27–2.15); other risk factors included age (1.06, 1.05–1.07), dementia (1.48, 1.10–1.99), and cancer (1.92, 1.56–2.36). MV/ECMO use was also significantly associated with higher expenditures (Exp[β]: 1.49, 95% confidence interval: 1.29–1.73); other risk factors included kidney disease (1.60, 1.29–2.01), cerebrovascular disease (1.74, 1.56–1.94), and cancer (1.28, 1.14–1.44). Survivors of severe COVID-19 who required MV or ECMO during hospitalization were associated with higher post-discharge mortality and expenditures, suggesting a need for targeted care to reduce their clinical and economic burden.